Effects of additives and coagulant temperature on fabrication of high performance PVDF/Pluronic F127 blend hollow fiber membranes via nonsolvent induced phase separation - Loh, Chun Heng (2013)
Poly(vinylidene fluoride) (PVDF) has become one of the most popular materials for membrane preparation via nonsolvent induced phase separation (NIPS) process. In this study, an amphiphilic block copolymer, Pluronic F127, has been used as both a pore-former and a surface-modifier in the fabrication of PVDF hollow fiber membranes to enhance the membrane permeability and hydrophilicity. The effects of 2nd additive and coagulant temperature on the formation of PVDF/Pluronic F127 membranes have also been investigated. The as-spun hollow fibers were characterized in terms of cross-sectional morphology, pure water permeation (PWP), relative molecular mass cut-off (MWCO), membrane chemistry, and hydrophilicity. It was observed that the addition of Pluronic F127 significantly increased the PWP of as-spun fibers, while the membrane contact angle was reduced. However, the size of macrovoids in the membranes was undesirably large. The addition of a 2nd additive, including lithium chloride (LiCl) and water, or an increase in coagulant temperature was found to effectively suppress the macrovoid formation in the Pluronic-containing membranes. In addition, the use of LiCl as a 2nd additive also further enhanced the PWP and hydrophilicity of the membranes, while the surface pore size became smaller. PVDF hollow fiber with a PWP as high as 2530 L·m -2·h -1·MPa -1, a MWCO of 53000 and a contact angle of 71°was successfully fabricated with 3 (by mass) of Pluronic F127 and 3 (by mass) of LiCl at a coagulant temperature of 25°C, which shows better performance as compared with most of PVDF hollow fiber membranes made by NIPS method.